Effects of dietary supplementation of A3α‐peptidoglycan on the growth, immune response and defence of sea cucumber Apostichopus japonicus. (13th December 2013) - Zhang, C.Y.; Chen, G.F.; C Wang, C.; Song, X.L.; Wang, Y.G.; Xu, Z.
Abstract To determine the effects of A3α‐peptidoglycan (A3α‐PG) extracted from Bifidobacterium sp. on the growth, immune response and disease resistance of sea cucumber Apostichopus japonicus, a 70‐day feeding trial was conducted in this study. A total of 216 sea cucumbers were fed with four practical diets prepared from a commercial feed with different contents (0, 1.5, 2.5 and 4.0 g kg−1) of A3α‐PG. The specific growth rate (SGR), total coelomocyte count (TCC), phagocytotic activity and activities of four immunological enzymes in both cell‐free coelomic fluid (extracellular, EC) and coelomocyte lysate supernatant (intracellular, IC), including acid phosphatase (ACP), alkaline phosphatase (ALP), peroxidase (POD) and superoxide dismutase (SOD), were measured at the end of the feeding trial. Finally, the animals were administered a 16‐day Vibrio splendidus challenge via intraperitoneal injection to test the potency of A3α‐PG on disease resistance. Compared with the control (0 g kg−1 A3α‐PG), a significant increase (P < 0.05) in SGR was observed in the groups fed with 1.5 and 2.5 g kg−1 A3a‐PG. The TCC, ranging from 7.25 × 106 to 1.05 × 107 cells mL−1, was not significantly affected (P > 0.05) by A3α‐PG, . Coelomocyte phagocytotic activities in all of the A3α‐PG‐supplemented groups were significantly activated (P < 0.05), but no significant difference (P > 0.05) was observed. Sea cucumbers fed with 1.5 and 2.5 g kg−1 A3α‐PG exhibited significant activation (P < 0.05) of EC/IC‐ACP, EC/IC‐ALP, and EC/IC‐POD activities. A significant increase in EC‐SOD activities (P < 0.05) was exhibited by all groups with A3α‐PG supplementation. The challenge test showed that animals fed with diets containing 2.5 and 4.0 g kg−1 A3α‐PG had significantly lower cumulative mortalities compared with the control 16 days after exposure. All of the results presented here show that A3α‐PG can positively enhance the growth, immune response and disease resistance of sea cucumber, suggesting that dietary supplementation of A3α‐PG has potential applications in the health management of economic species of sea cucumber.